ORAL ABSTRACTS: THERAPEUTIC PLENARY: OR-THER-02: Endoscopic ultrasonography-guided biliary drainage: A meta-analysis of publications with fifty or more patients - Almadi, Majid (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Endoscopic ultrasound-guided biliary drainage (EUS-BD) is an alternative to percutaneous drainage when endoscopic retrograde cholangiopancreatography (ERCP) is not possible or has failed. This was a meta-analysis determining the success and safety of EUS-BD and comparing techniques. METHODS: Full-text publications where more than 50 patients were reported were included. Primary outcomes were technical success, clinical success, and overall complications. Secondary outcomes were incidence of bile leaks, bleeding, cholangitis, perforation, pneumoperitoneum, and death. RESULTS: Nine trials were included (576 patients). EUS-BD had a technical success of 89.45% (95% confidence interval [CI], 81.26, 97.63), clinical success 81.69% (95% CI, 65.30, 98.08), total complications 20.58% (95% CI, 10.26, 30.89), bile leaks 5.97% (95% CI, 2.23, 9.71), bleeding 4.8% (95% CI, 0.15, 9.45), cholangitis 3.18% (95% CI, 1.39, 4.96), perforation 1.56% (95% CI, 0.30, 2.82), pneumoperitoneum 3.53% (95% CI, 0.73, 6.33), and death 1.6% (95% CI, 0.00, 3.50). Comparing EUS-choledochoduodenostomy (EUS-CDS) to EUS-hepaticogastrostomy (EUS-HG), the latter had a higher rate of overall complications, odds ratio (OR) 2.04 (95% confidence interval [CI], 1.21, 3.44). There was no difference comparing EUS-CDS versus EUS rendezvous (EUS-RV), EUS-CDS versus EUS antegrade stenting, or EUS-HG versus EUS-RV. Hepatic access versus extrahepatic access had a higher complication, OR 1.49 (95% CI, 1.02, 2.07). CONCLUSIONS: A transhepatic approach and EUS-HG might have a higher overall complication rate, but data are limited.